Clinical Significance of BRAF and ZEB2 Expressions in Healthy Adjacent Tissue of Bladder Cancer - Shima Hosseini; Massoud Saidijam; Hamid Eslami; Ali Reza Soltanian; Seyed Habibollah Mousavi-Bahar; Ali Mahdavinezhad (Middle East Journal of Cancer, 2019)
Background: Numerous molecular changes are involved in the development and progression of bladder cancer. Regular follow-up of patients is crucial due to the high recurrence rate of bladder cancer. The aim of this study is to determine the role of B-Raf proto-oncogene, serine/threonine kinase and ZEB2 expressions in onset and progression of bladder cancer. We have also investigated their relationships to pathological characteristics. Methods: We conducted this case-control study on bladder cancer and its healthy adjacent tissue, and normal bladder tissue from patients with benign prostatic hyperplasia. After extraction of total RNA and cDNA synthesis, quantitative expression analysis was performed in duplicate using real-time PCR. Changes in the gene expression were calculated according to the 2(-ΔΔCt) equation. The products were confirmed by 1% agarose gel electrophoresis and sequenced by Bioneer Company. Data was analyzed using the SPSS software (version 16). Results: There was significantly greater B-Raf proto-oncogene, serine/threonine kinase expression in 82% of bladder tumor samples compared to the adjacent tissues. In 91.1% of tumor samples, the gene expression was also significantly higher than healthy bladder tissues from patients with benign prostatic hyperplasia. We observed overexpression of B-Raf proto-oncogene, serine/threonine kinase in 61.7% of the healthy margin tissue samples compared to healthy bladder tissues of patients with benign prostatic hyperplasia (P<0.001). Expression of ZEB2 in 52.9% of the bladder tumor samples was significantly higher than healthy peripheral tissues. This increase was observed in 94.1% of tumor samples compared to healthy bladder tissues of patients with benign prostatic hyperplasia (P<0.001). Pearson correlation coefficient showed a positive relationship between B-Raf proto-oncogene, serine/threonine kinase and ZEB2 in cancerous samples (r = 0.75) and healthy margin tissue samples (r = 0.49). Conclusion: During the carcinogenesis process, molecular changes are seen in healthy margin tissue. These molecular changes may be the reason for the high recurrence rate of bladder cancer. B-Raf proto-oncogene, serine/threonine kinase can potentially be a target cancer therapy in antisense technologies.